The Effect of Compare-Diagnose-Operate (CDO) Strategy to Improve Students’ Writing Ability In Descriptive Text - Tatang Kusuma; Ali Akbarjono; Fera Zasrianita (Yayasan Karinosseff Muda Indonesia, 2021)
This study aims to determine the differences in cognitive learning outcomes (in the form of pre-test and post-test scores) of students in class X IPS 1 as a control class and class XI MIPA 3 as experimental class at SMA N 5 Bengkulu Tengah, by providing treatment using the Compare -Diagnose-Operate (CDO) strategy. This type of research is Quasi Experiment. The population is tenth grade students of SMA N 5 Bengkulu Tengah with 368 students. From this population, 37 students were taken as samples. Each class is 17 students XI IPS 1 and 20 students XI MIPA 3. Research data were collected through writing tests and documentation. The results showed a significant change in the experimental class with an average value of 71.85 while in the control class an average value of 52.06. The post-test results show that the Compare-Diagnose- Operate (CDO) strategy can improve students' writing skills. Thus, the Compare- Diagnose-Operate (CDO) strategy can be one of effective strategy to increase students‟ writing ability.